PKU organises IFitER programme to tackle obesity - Nor Salwana, Mohammad Idris (2022)
PEKAN, 22 September 2022 - Universiti Malaysia Pahang Health Centre (UMP) has recorded a total of 579 UMP staff categorised as having a risk of non-communicable diseases, i.e., abnormal lipid profile as well as level 1 and level 2 obesity through staff health screening tests (mobile clinic) conducted in 2020.